Phytochemical and Antioxidant Activity of Akway (Drymis piperita Hook f.) Stem Bark Ethanol Extract - Angela Myrra Puspita Dewi; Umar Santoso; Yudi Pranoto; Djagal Wiseso Marseno (Advance Sustainable Science Engineering and Technology, 2024)
The amount of solvent affects the effectiveness of the extraction, so the chemical components are extracted entirely from the plant. This study investigated the best ratio of Akway bark : solvent (ethanol) to produce Akway extract with the highest antioxidant activity. Extraction with the treatment of Akway skin: ethanol ratio of 1:2; 1:4; 1:6 (b/v) was carried out and then the results were tested for total phenolic and flavonoid content and antioxidant activity. The best Akway bark:ethanol ratio was obtained at 1:4 (b/v) ratio with 9.54% extract yield, 289.57 mg GAE/g total phenolic content, 185.47 mg eq quercetin/g total flavonoids. Akway bark extract has potential as a source of antioxidants as indicated by its high antioxidant activity with DPPH free radical scavenging and ferric reducing activity of 50% (IC50) at extract concentrations of 16.59 µg/mL extract and 60.93 µg/mL extract, and carotene bleaching inhibition activity of 85.76%. There are 4 types of phenolic compounds and 4 types of flavonoid compounds identified with the highest percentage of components, namely Pereniporin B (57%).